Savonetta Bay and St. Mary's Point, Trinidad - (:unkn) unknown (My University, 2011)
A picture showing the waters of Savonette Bay and rolling headland of St. Mary's Point.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Coasts; St. Mary's Point; Savonetta Bay; Bays--Trinidad and Tobago